KIR2DL4 (CD158d): An activation receptor for HLA-G - Rajagopalan, Sumati; Long, Eric O. (Frontiers in Immunology, 2012)
KIR2DL4 is an unusual KIR family member in terms of its structure, expression, cellular localization and signaling properties. The most conserved KIR in evolution, it is referred to as a framework KIR gene and is expressed by all natural killer cells and a subset of T cells. Although it has a long cytoplasmic tail that is typical of inhibitory KIR, engagement of this receptor results in the activation of NK cells, not for cytotoxicity, but for cytokine and chemokine secretion. Unlike all other KIRs, which are expressed on the surface of NK cells, KIR2DL4 resides in endosomes. It signals from this intracellular site for a proinflammatory and proangiogenic response, using a novel endosomal signaling pathway that involves the serine/threonine kinases DNA-PKcs and Akt. The only known ligand of KIR2DL4 is HLA-G. Soluble HLA-G accumulates in KIR2DL4+ endosomes. Unlike classical HLA molecules that serve as ligands for other KIR family members, in healthy individuals, HLA-G expression is restricted to the fetal trophoblast cells that invade the maternal decidua during early pregnancy. Since NK cells constitute the predominant lymphocyte subset at this site, the proinflammatory/proangiogenic outcome of the interaction between KIR2DL4 and soluble HLA-G supports a role for KIR2DL4 in the extensive remodeling of the maternal vasculature during the early weeks of pregnancy.